Correlation Of Temperature Humidity Index With Milk Yield Of Crossbred Jersey Cows - Henry, A. Clement Ebenezer; Arunachalam, S.; Sivakumar, T.; Jagatheesan , P.N. Richard (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The study was carried out in the herd of Jersey-Sindhi crossbred cows maintained at Livestock Research Station, Kattupakkam, mostly a semi-arid region. The temperature-humidity index (THI) was calculated by applying dry bulb reading and wet bulb reading. The THI calculated for morning and evening during winter were 74.35 ± 0.23, 77.43 ± 0.35 respectively and in summer were 83.39 ± 0.32 and 85.99 ± 0.31 respectively and the differences were found to be highly significant (P< 0.01) between seasons. The overall average milk yield per day during lactation of Jersey-Sindhi was 5.52 ± 0.19 kg and average milk yield per day from calving to calving was 4.66 ± 0.23 respectively. The THI and average daily milk yield per cow for both winter and summer were negative correlated but had no significant effect. Even though the THI was above the comfort level, it had little or no effect on the milk yield of crossbred Jersey-Sindhi cattle since the animals in the experimental condition were found to be tolerant to the climatic condition prevailing in that area.